Madrasah Principal's Strategy in the Development of Religious Culture in the School Environment - Muhamad Qulyuby; Selnistia Hidayani (PT. Intelek Cendikiawan Nusantara, 2025)
The development of religious culture is one of the strategic efforts in strengthening the character of students and creating a madrasah environment that is conducive to the development of Islamic values. The head of the madrasah has a central role in directing, moving, and ensuring that all school residents are involved in the formation of the culture. This study aims to analyze the strategies of madrasah heads in developing religious culture in the school environment by reviewing the concept of Islamic education leadership, organizational culture, and effective madrasah management practices. The research method uses a library research approach through searching literature from books, scientific journals, educational regulations, and relevant previous research results. The results of the study show that the strategy of madrasah heads includes exemplary practices in worship and morals, integrating religious values in school policies and programs, habituating sustainable religious activities, and strengthening cooperation with teachers, education staff, students, and parents. Madrasah heads who implement visionary and participatory leadership have proven to be more successful in building a religious culture that has character, internalized, and sustainable. These findings confirm that the success of religious culture is highly determined by the commitment and strategic role of madrasah heads.